2015
DOI: 10.3109/10717544.2015.1045103
|View full text |Cite
|
Sign up to set email alerts
|

In vivo pharmacokinetics, biodistribution and antitumor effect of paclitaxel-loaded micelles based on α-tocopherol succinate-modified chitosan

Abstract: In our previous study, a-tocopherol succinate modified chitosan (CS-TOS) was synthesized and encapsulated paclitaxel (PTX) to form micelles. Preliminary study revealed that the CS-TOS was a potential micellar carrier for PTX. In this study, some further researches were done using Taxol formulation as the control to evaluate the micelle system deeply. In vitro cell experiments demonstrated that the cytotoxic effect of PTX-loaded CS-TOS micelles against MCF-7 cells was comparable with that of Taxol formulation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…The in vivo antitumor activity of PTX-loaded FA-CS-DA micelles was evaluated in H22 tumor-bearing mice. To establish the tumor model, mice were inoculated subcutaneously in the right armpit with 5 × 10 6 cells (0.2 mL) [ 36 ]. When the tumor xenografts became palpable, the mice were randomly divided into 2 groups ( n = 6) and treated with physiological saline and PTX-loaded FA-CS-DA micelles (15 mg/kg), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The in vivo antitumor activity of PTX-loaded FA-CS-DA micelles was evaluated in H22 tumor-bearing mice. To establish the tumor model, mice were inoculated subcutaneously in the right armpit with 5 × 10 6 cells (0.2 mL) [ 36 ]. When the tumor xenografts became palpable, the mice were randomly divided into 2 groups ( n = 6) and treated with physiological saline and PTX-loaded FA-CS-DA micelles (15 mg/kg), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the micellar formulations, NK911 and Genexol-PM, have already advanced to the clinical trials (Matsumura, 2006;Ahn et al, 2014). Thanks to their distinctive core-shell structure, polymeric micelles possess high loading capacity of poorly water-soluble drugs within the hydrophobic inner core; whereas the hydrophilic corona confers aqueous solubility and steric stability, which also protects the encapsulated drug from inactivation in gastrointestinal components (Croy & Kwon, 2006;Liang et al, 2015). Importantly, due to the small size of micelles, previous reports described that the drugloaded nanoparticles could be absorbed in intact form by enterocytes or M cells via endocytic pathway after oral administration (Mathot et al, 2007;Li et al, 2010;Al-Hilal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…To determine the accumulated PTX in tumors and normal tissues at 24 and 48 h after intravenous administration of PTX-based formulations at 10 mg/kg PTX equivalent, the tissue samples were processed according to the previous study by Liang et al [ 21 ] and the results were shown in Figure 5C . After administration for 24 and 48 h, the accumulations of DEX-IND/PTX and DEX-SS-IND/PTX in tumors were significantly enhanced compared with Taxol.…”
Section: Resultsmentioning
confidence: 99%